Safe Management of Pressure Equipment/Assemblies in Biorefineries: Case Study of a Reactor - Antonino Muratore; Giovanni Grillone; Sabrina Copelli; Roberto Lauri; Nicola Altamura; Giuseppe Giannelli; Vincenzo Nastasi (Chemical Engineering Transactions)
In Europe some companies have started to modify part of their processes to allow the production of biofuels from oily biomass (green setup). Considering both the new production processes and the new type of loaded fluid (oily biomass), the user will have to manage the residual risk of the pressure equipment/assemblies (vessels, exchangers, reactors, pipes, etc.). In order to manage such risks, some steps are required:Step 1: Nowadays, in EU, all pressure equipment/assemblies must be both designed and built according to PED Directive. PED Directive shall apply to the design, manufacture and conformity assessment of pressure equipment and assemblies with a maximum allowable pressure, which is greater than 0,5 barg. In particular, it concerns the certification of products and components, the qualification of materials, personnel, and processes. Step 2: In addition to design and manufacture, attention must be also paid to aspects related to installation, use and any reasonably foreseeable improper use, identified by the manufacturer in the use and maintenance manuals, considering the complexity and danger in all operating conditions of the plant. Each EU Member State, which is subject to minimum safety and health requirements, regulates commissioning and operation with its own legislation. In Italy commissioning and operation are regulated by Ministerial Decree 329/04, Legislative Decree 81/08 and Ministerial Decree 11/04/2011. Step 3: In the event that these establishments are regulated by the Seveso Directive, the operator should have a general obligation to take all necessary measures to prevent major accidents, to mitigate their consequences and to take recovery measures. The operator must identify also the critical elements for safety and environment in order to prevent major accident hazards. In Italy, the Seveso Directive was implemented with Legislative Decree 105/15. Furthermore, in case of flammable gases/vapours or combustible dusts presence, in accordance with ATEX Directive, the employer is obliged to classify the areas, where potentially explosive atmospheres could occur. Considering the three steps described above, the authors propose, through a case study, appropriate measures to ensure a put into service of a reactor in an establishment for the production of biofuels from oily biomass.